KETERKAITAN RELIGIUSITAS, GENDER, LoM DAN PERSEPSI ETIKA PENGGELAPAN PAJAK - Sofha, Dewi; Utomo, St. Dwiarso (Sekolah Tinggi Ilmu Ekonomi Totalwin, 2018)
Tax evasion could be seen as an ethical deed or not depends on several factors. They are among others: gender, religiosity and Love of Money (LoM). The goal of the current research is to examine the effect of gender, religiosity, and LoM towards tax evasion ethical perception. The population of the research is undergraduate (S1) accounting students of private universities in Semarang. The sample used in the researchcovers the undergraduate accounting students of Dian Nuswantoro University, Soegijapranata Catholic University, Sultan Agung Islamic University, State University of Semarang, and University of Muhammadiyah Semarang. The sampling technique used in the research is accidental sampling. As much as 100 questionnaires have been delivered to the chosen respondents and all of them are declared properly to use. The analysis results using Smart-Partial Least Squares (PLS) 3.0 model show that gender and religiosity have impact on tax evasion ethical perception, however LoM does not. The results of the research show that religiosity and LoM do not mediate the relationship between gender and tax evasion ethical perception.